THE INFLUENCE OF BRAND AWARENESS, BRAND TRUST AND SALES PROMOTION ON DECISIONS TO PURCHASE LE MINERALE PACKAGED DRINKING WATER (AMDK) IN DKI JAKARTA - Arina Izataki; Suadi Sapta Putra; Kumba Digdowiseiso (SEAN Institute, 2023)
This research aims to determine the influence of brand awareness, brand trust and sales promotion on purchasing decisions for Le Minerale bottled drinking water (AMDK) in DKI Jakarta. The sample and research consisted of 100 respondents who made purchasing decisions in DKI Jakarta. This research uses primary data with data collection methods through questionnaires distributed to 100 respondents. The data analysis technique uses inferential analysis with multiple linear regression and uses the Statistical Product and Service Solution (SPSS) version 23.0 program. From the results of the t test, this research shows that Brand Awareness (X1) has a positive and significant influence on purchasing decisions. This can be seen from the results of the t test where (tcount is 6.694 > 1.660 t table) and its significance is (0.000 < 0.05). Brand Trust (X2) has a positive and significant influence on Purchasing Decisions, this can be seen from the results of the t test where (tcount 2.931 > 1.660 ttable) and its significance (0.004 < 0.05). Sales Promotion (X3) has a positive and significant influence on Purchasing Decisions, this can be seen from the results of the t test where (tcount 2.115 > 1.660 ttable) and its significance (0.037 < 0.05). In this way, it can be concluded that Brand Awareness, Brand Trust and Sales Promotion have a positive and significant influence on purchasing decisions.